Evaluasi Sifat Kimia dan Sensoris Nata De Coco dengan Penambahan Ekstrak Buah Naga (Hylocereus polyrhizus) - Meldayanoor Meldayanoor; Mariatul Kiptiah; Yuliana Ningsih; Titis Linangsari; Ema Lestari; Jesi Yardani; Almira Ulimaz; Muhammad Indra Darmawan; Mufrida Zein; Marlia Adriana; Agung Nugroho; Luthfina Ariyani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2023)
Nata de coco is a product resulting from a fermentation process from coconut water with the help of Acetobacter xylinum. To increase the functional value and taste of nata de coco, you can add red dragon fruit extract. This study aims to evaluate the chemical and sensory properties of nata de coco which did not have dragon fruit extract added (P0) and nata de coco which had dragon fruit extract added (P1). Parameters for observing chemical properties include water content, protein, vitamin C and fiber. Sensory evaluation was carried out using a hedonic test using 30 panelists, the parameters observed were aroma, texture, taste and color. Based on the results of the evaluation of the chemical and sensory properties of nata de coco to which dragon fruit extract was added, it can be concluded that the addition of dragon fruit extract can increase protein levels (1.57%) and vitamin C (0.25%), and reduce water content (93.16%) and fiber content (1.20%). Meanwhile, the hedonic test showed that the panelists preferred the texture, aroma and taste parameters of nata de coco without adding dragon fruit extract. In terms of color parameters, panelists preferred nata de coco with added dragon fruit extract.